"She is my teacher and if it was not for her I would be dead" : exploration of rural South African Community Health Worker's informational and mediating roles in the home - Zulliger, Rose Ellen (Department of Public Health and Family Medicine, 2015)
This thesis seeks to fill the gap in the literature by exploring CHW IEC roles through: a protocol for the Health Information in the Home (HIH) study of the quality of IEC services by Community Care Workers; a structured literature review of the current state of the evidence and a journal manuscript based on the HIH study findings.